2018
DOI: 10.1088/1757-899x/349/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of gelatin from catfish bone using NaOH and its utilization as a template on mesoporous silica alumina

Abstract: Gelatin extraction from catfish bone using NaOH and its utilization as a template on a synthesis of mesoporous silica-alumina had been investigated. The extraction was prepared by immersing 25 g catfish bone in 125 mL of NaOH in concentration of 0.0; 0.05; 0.10; 0.15 and 0.20 M for 24 h, then washing with demineralized water until pH 7, followed by immersed the bone into 125 mL of 1 M HCl for 1 h, then washed using demineralized water into pH 5. To produce gelatin the bone was refluxed with 100 mL demineralize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…This result indicated that catfish bone gelatin has several functional groups similar to commercial gelatin . This result was different from another research about gelatin catfish bone by Nuryanto 15 , that claimed catfish bone gelatin has functional group of C=O, C-N, =C-N, NH and CH 2 .…”
Section: Fig 5 Ftir Of Commercial Gelatincontrasting
confidence: 94%
“…This result indicated that catfish bone gelatin has several functional groups similar to commercial gelatin . This result was different from another research about gelatin catfish bone by Nuryanto 15 , that claimed catfish bone gelatin has functional group of C=O, C-N, =C-N, NH and CH 2 .…”
Section: Fig 5 Ftir Of Commercial Gelatincontrasting
confidence: 94%
“…Different sources of gelatin and different curing treatment resulted in different molecular weights of gelatin proteins. The iridescent shark fishbone treated with HCl and NaOH resulted in 116-200 kDa gelatin proteins (Mahmoodani et al, 2014), while the iridescent shark fishbone with citric acid pre-treatment resulted in 38-162 kDa gelatin proteins (Pertiwi et al, 2018), iridescent shark fishbone with pineapple waste treatment resulted in 75-225 kDa gelatin proteins (Atma et al, 2018), and iridescent shark fishbone with 0.1 M NaOH immersion resulted in 25-200 kDa gelatin proteins (Nuryanto et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…African catfish (Clarias gariepinus, Burchell 1822) is one of the important cultured fish species extensively consumed by Indonesian people (1). However, to date, studies related to African catfish in Indonesia are still limited to fish feed formulations (2,3), aquaculture techniques (4), genetic improvement (5), and processed products (6).…”
Section: Introductionmentioning
confidence: 99%